TINDAK ILOKUSI BAHASA INDONESIA DALAM INTERAKSI KELUARGA - Alif Mudiono (Center of Language and Cultural Studies, 2014)
This study is a case study using multi-sites since the sources of data consisted of five couples of young families having interpersonal relationships between parents and children in the family. Design of this study is communication ethnography and pragmatics. These two designs brought about the following methodological implications: firstly, the interpretation of Indonesian illocutionary act in family interaction was based on emic perspective, and secondly, the meaning of the Indonesian illocutionary act in family interaction was based on more process-based rather than product-based discourse. Data of the study were two types: (1) the data taken from the speech acts, and (2) the data taken from field notes. These two types of data were collected through recording, observation, and interview. The data were collected and than analyzed by using an interactive model. The technique of analyzing data were done through four steps: (1) data collection, (2) data reduction, (3) data display, and (4) conclusion drawings.